2014
DOI: 10.3846/2029882x.2014.957902
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Prestress Losses on the Anchorage Zone of Prestressed Concrete Member / Įtemptųjų Gelžbetoninių Elementų Įtempių Nuostolių Įtaka Inkaravimo Zonai

Abstract: Abstract. Article briefly discusses the factors affecting bond between concrete and reinforcement of prestressed concrete member. Behavior of prestressed concrete member during release of reinforcement is discussed. Comparative analysis of equations, which describes relation between strand draw-in and transfer length, is presented. Article analyses distribution of loss of prestress at the anchorage zone of prestressed concrete member. Estimation of rational position of strands at the anchorage zone of flexural… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Proceedings from 22nd Czech Concrete Day 2015 F 0,05 load in sleeper reinforced with 10,5 mm diameter bars was higher up to 13% under static load and up to 6% under dynamic load comparing with sleepers reinforced with 9,6 mm diameter bars. F 0,05 load in sleeper D2 (10,5) was lower by 6% than in sleepers with lower reinforcement ratio.…”
mentioning
confidence: 71%
See 1 more Smart Citation
“…Proceedings from 22nd Czech Concrete Day 2015 F 0,05 load in sleeper reinforced with 10,5 mm diameter bars was higher up to 13% under static load and up to 6% under dynamic load comparing with sleepers reinforced with 9,6 mm diameter bars. F 0,05 load in sleeper D2 (10,5) was lower by 6% than in sleepers with lower reinforcement ratio.…”
mentioning
confidence: 71%
“…Tension force is introduced to concrete through the transmission length (L T ) (Fig. 2) and initial stresses are affecting bond of reinforcement during release [10] . Additional tension force induced by service loads is introduced to prestressing reinforcement during exploitation.…”
mentioning
confidence: 99%
“…Loading from the oil and other input material and geometric characteristics were considered as deterministic using the values listed in the previous chapters. Numerous modern approaches exist for the study of the effect of input parameters of mathematical computational models on their outputs; see for e.g., [14][15][16][17][18][19][20]. The effects of the variability of input random variables described in Table 1 on the variability of von Mises reduced stresses were studied in this article.…”
Section: Sensitivity Analysismentioning
confidence: 99%
“…Generally, the bond stress-slip relationship between the reinforced bar and concrete usually refers to the relationship between the average bond stress and the slip at the free end. Moreover, some researchers have studied bond stress distribution along the length direction in the anchorage zone of RC specimens (Jokūbaitis et al, 2014;Jokūbaitis et al, 2017). It is shown that the distribution curve of bond stress in the bond section gradually becomes flat with the corrosion of the reinforced bars (Zhao et al, 2013).…”
Section: Introductionmentioning
confidence: 99%